1986
DOI: 10.1111/j.1365-2125.1986.tb05194.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intra‐articular steroids on plasma salicylate concentrations.

Abstract: 1 Plasma salicylate concentrations and salicylate clearances were evaluated in 10 patients before and then 3 days after the intra-articular administration of glucocorticoid steroids.All patients were on chronic salicylate treatment, the dosage varying from 1.3-4.6 g day-1 of enteric-coated aspirin. 2 The mean steady state plasma concentration (+ s.e. mean) of salicylate decreased significantly after intra-articular steroid (90.9 + 14.8 mg 1-1 -64.7 + 8.9, P < 0.05), whilst the mean clearance increased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, given a significance level of 0.05 and a 1 value of 0.8, this study with six subjects should have been able to detect at least a 20% increase in the clearance of salicylate induced by corticosteroids (Dobson, 1984). An increase in salicylate clearance of the order of 25-59% was anticipated from data reported in previous studies (Graham et al, 1977;Kiinenberg & Miller, 1965;Koren et al, 1987;Edelman et al, 1986). However, since most of the subjects had decreases in clearance of 10% or less, it would seem most unlikely that increasing patient numbers would unmask a substantial and significant increase in salicylate clearance.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, given a significance level of 0.05 and a 1 value of 0.8, this study with six subjects should have been able to detect at least a 20% increase in the clearance of salicylate induced by corticosteroids (Dobson, 1984). An increase in salicylate clearance of the order of 25-59% was anticipated from data reported in previous studies (Graham et al, 1977;Kiinenberg & Miller, 1965;Koren et al, 1987;Edelman et al, 1986). However, since most of the subjects had decreases in clearance of 10% or less, it would seem most unlikely that increasing patient numbers would unmask a substantial and significant increase in salicylate clearance.…”
Section: Discussionmentioning
confidence: 72%
“…Salicylate concentrations in plasma increased markedly when corticosteroid dosage was tapered in patients with rheumatoid arthritis (Klinenberg & Miller, 1965;Muirden & Barraclough, 1976) and, correspondingly decreased when prednisone was commenced (Koren et al, 1987). In addition, it was noted that salicylate concentrations were substantially lower when corticosteroids were taken concurrently (Graham et al, 1977;Bardare et al, 1978) while, in a recent communication, it was reported that even intra-articular corticosteroids decreased the plasma concentrations of salicylate during chronic salicylate therapy (Edelman et al, 1986). Klinenberg & Miller (1965) reported that corticosteroids enhanced the renal clearance of salicylate in some patients but their assay method was non-specific and salicylate could not be distinguished from its major urinary metabolite, salicylurate, which is found in high concentration in the urine (Levy et al, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…According to Edelman et al (38) prednisolon, DEX and methylprednisolon as well as other glucocorticoids (39,40) decreased the serum salicylate concentrations as a result of increased salicylic clearance caused by glucocorticoids. Klinenberg and Miller (41) supposed that glucocorticoids increased glomerula filtration of salicylates.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids Concurrent administration of aspirin or salicylic acid with a glucocorticoid (orally or via intraarticular injection) leads to increased salicylate clearance accompanied by a significant reduction Drug Safety 8 (2) 1993 in plasma salicylate concentrations (Baer et al 1987;Edelman et al 1986;Koren et al 1987). Further support for this interaction derives from reports that plasma salicylate concentrations rise proportionately with a reduction in the daily dose of corticosteroids when both drugs are coadministered (Klinenberg & Miller 1965;Muirden & Barraclough 1976).…”
Section: Cholestyraminementioning
confidence: 93%